Cooling performance of vortex generator - Halder, Nirmal (Institute of Advanced Engineering and Science, 2021)
Present numerical investigation proposes to mitigate the effects of CRVP by employing a pair of vortex generator.Â Numerical simulation has been carried out to investigate the effect of placement of vortex generator on the characteristics of film cooling effectiveness. Various configuration has been taken based on vortex generator location at upstream, downstream of circular film cooling hole. Along with these utilizing multiple vortex generator at different downstream location also has been detected. The jet to cross flow blowing ratios (M = Ïjuj / Ïcfucf)Â is maintained at unity while Reynolds number based on free stream velocity and film cooling hole dimension is kept at 17000. The investigation of suitable turbulence model has been studied. The results are compared with baseline case. The numerical investigation is accomplished implementing FLUENT commercial code adopting the K-omega SST model. Among configuration E and all quantity (DR, M, RE and TI) better CRVP distribution is depicted for TI and lowest for configuration E.